Can age make a difference? A moderated model of altruistic organizational citizenship behaviour antecedents - Silvia Profili; Alessia Sammarra; Laura Innocenti (International Journal of Business Science & Applied Management (IJBSAM), 2016)
This paper utilizes lifespan approaches to examine how the effects of fun at work, work-life balance, and perceived supervisor support on altruistic Organizational Citizenship Behaviour (OCB) are moderated by age. Based on multilevel analysis of a large sample of 6,182 employees in 37 companies, fun at work significantly predicted altruism towards co-workers for young employees only, while work-life balance predicted altruistic behaviours for mid- and old-age group employees. Contrary to expectation, age did not moderate the relationship between perceived supervisor support and altruism. These findings suggest further exploration is needed on how age qualifies the relationship between altruistic OCB and its antecedents. This is an especially crucial issue in light of demographic trends indicating further extension of employees' working lives.
Keywords: 650; Altruistic organization citizenship behaviour; age; fun at work; work-life balance; perceived supervisor support